Investigation of the interaction of charge motion and residual gas concentration in an optically accessible SI engine - Mederer, Thomas; Trost, Johannes; Storch, Michael; Zigan, Lars; Wensing, Michael; Leipertz, Alfred (11th International Conference on Engines & Vehicles: ICE 2013, 2013)

Investigation of the interaction of charge motion and residual gas concentration in an optically accessible SI engine - Mederer, Thomas; Wensing, Michael; Leipertz, Alfred (SAE Technical Papers, 2013)
In spark-ignition engines, high exhaust gas recirculation (EGR) rates have demonstrated their potential in reducing fuel consumption and emissions. However, irregular combustion at high residual gas concentrations limits the EGR rates. The following study presents a strategy that has been developed to investigate the influence of complex charge motion on mixture formation and combustion for high residual gas concentrations with the aim of extending these limits. An optically accessible single-cylinder SI Engine with direct injection was used to measure the charge distribution by means of laser induced fluorescence (LIF). A special device inside the inlet pipe gave the possibility to generate a defined swirl motion overlaying a tumble motion given by the design of the inlet ports. A developed uniformity index to evaluate the LIF results and an adjustable supply of premixed residual gas into the intake air system helped to study the effect of increasing EGR rates on charge distribution and combustion for different charge motions. The tracer acetone was injected into the intake air system to localize residual gas in the combustion chamber. Results obtained in typical part load operation show fastest mixing and most stable burning at high EGR rates for a charge motion combining a standard tumble flow with additional swirl. Copyright © 2013 SAE International.
Created from Fastlane, Scopus look-up

Investigations on a new engine concept for small hydrogen power generation units using LOHCs - Schumacher, Moritz; Mederer, Thomas; Wensing, Michael (SAE Technical Papers, 2013)
New energy scenarios for decentralised stationary energy supply based on Liquid Organic Hydrogen Carriers (LOHC) offer an attractive application for hydrogen engines and are a reason why hydrogen engines become topical again. Since hydrogen stored in LOHCs is released under ambient pressure and temperatures of over 200°C, compression and cooling of the hydrogen is needed, lowering the system's overall efficiency. Direct injection of hydrogen is advantageous due to its low volumetric energy density and the tendency towards pre-ignition. The development objective is an injection and combustion strategy for an engine in the performance category below 15 kW and the described fuel supply scenario. Therefore, an one dimensional simulation model of the engine and the hydrogen supplying compressor was built. The simulation results show a large influence of the injection pressure on engine efficiency due to the hydrogen supplying compressor. For the studies presented here an engine with an extended expansion was built for an increased utilisation of exhaust gas enthalpy. The extended expansion was also implemented in the one dimensional simulation model. First results show enhanced indicated efficiency under high load conditions. Furthermore, preliminary investigations on hydrogen combustion have been carried out using an optically accessible hydrogen engine. Laser-induced fluorescence was applied to investigate the effect of varied injection pressures and timings on the processes of injection, mixture formation and combustion. The end-of-injection timing variation showed that approx. 90 °CA are necessary to generate a homogeneous mixture in the combustion chamber which limits the injection timing for homogeneous combustion concepts. Copyright © 2013 SAE International and Copyright © 2013 KSAE.
Created from Fastlane, Scopus look-up

Laser-Induced Fluorescence to Visualize Gas Mixture Formation in an Optically Accessible Hydrogen Engine - Mederer, Thomas; Wensing, Michael; Leipertz, Alfred (Eighth International Conference on Modeling and Diagnostics for Advanced Engine Systems, 2012)

Laser-Optical and Numerical Study of Mixture Formation in a GDI Engine with High Tumble Motion - Neumann, S.; Hasse, C.; Grasreiner, S.; Kleemann, A.; Hussmann, B.; Heinisch, A.; Durst, B.; Koch, Peter; Mederer, Thomas; Knorsch, Tobias; Wensing, Michael (Thermo and fluid dynamic processes in direct injection engines, 2012)

LIF Laser Scanning zur Untersuchung der Gemischbildung in Motoren mit reduziertem optischen Zugang - Welß, Richard; Bornschlegel, Sebastian; Heldmann, Markus; Wensing, Michael; Mederer, Thomas (Motorische Verbrennung – Aktuelle Probleme und moderne Lösungsansätze (XII. Tagung), 2016)

Mixture formation in DISI Engines investigated for conventional multi-hole and colliding-jet injectors by a new LIF technique - Welß, Richard; Mederer, Thomas; Heldmann, Markus; Wensing, Michael; et al. (THIESEL 2014 Conference on Thermo- and Fluid Dynamic Processes in Direct Injection Engines, 2014)

Simultaneous spatially resolved visualization of fuel/air ratio and residual gas distribution in an optically accessible SI engine - Mederer, Thomas; Friedrich, Wolfgang; Trost, Johannes; Zigan, Lars; Wensing, Michael (14. Internationales Stuttgarter Symposium, 2014)

Untersuchung der Gemischbildung in einem optisch zugänglichen Wasserstoffmotor mittels laserinduzierter Fluoreszenz - Wensing, Michael; Mederer, Thomas; Leipertz, Alfred (Haus der Technik - International Congress Motorische Verbrennung Engine Combustion Aktuelle Probleme und moderne Lösungsansätze (XI. Tagung), 2013)

Untersuchung der Wechselwirkung von Ladungsbewegung, Gemischbildung und Restgaskonzentration am DI-Ottomotor - Mederer, Thomas (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)
Die vorliegende Arbeit beschreibt die Entwicklung einer methodischen Vorgehensweise, um die Auswirkung einer gezielt beeinflussten Ladungsbewegung auf die Gemischbildung, die Temperaturund Restgasverteilung sowie die anschließende Verbrennung in direkteinspritzenden Ottomotoren untersuchen zu können. Neben der Realisierung einer definierten Ladungsbewegung unter Verwendung verschiedener Ladungsbewegungsklappen und einer Restgaszuführung an den untersuchten optisch zugänglichen Motoren zeichnet sich diese methodische Vorgehensweise durch verschiedene optische Messtechniken aus. Um die Auswirkung der Ladungsbewegung auf die Gemischbildung darzustellen, wurde die laserinduzierte Fluoreszenz eingesetzt und ein Gleichverteilungsindex angewendet, der den Grad der Homogenisierung der LIF-Ergebnisbilder quantifiziert. Zur Darstellung des Einflusses der Ladungsbewegung auf die Verbrennung beinhaltet diese Vorgehensweise die OH-Chemilumineszenz Messung in Kombination mit der Auswertung der Indizierdaten und einer Brennverlaufsanalyse in GT- Power. Da bisher keine Möglichkeit existierte, das Luft/Kraftstoff-Verhältnis, die Temperatur- und die Restgasverteilung im Brennraum simultan zu detektieren, wurde mit der Zweiwellenlängen-Zweifarben- LIF als letzter Schritt dieser Vorgehensweise eine Messtechnik auf Basis der bereits erfolgreich eingesetzten Zweiwellenlängen-LIF Technik entwickelt, die unter Verwendung zweier Excimer-Laser, zweier intensivierter CCD-Kameras und dem simultanen Einsatz zweier Tracer (Triethylamin als Kraftstofftracer und Aceton als Tracer für die Frischluft) eine simultane Detektion aller drei Größen ermöglicht. Zur Qualifizierung der Zweiwellenlängen-Zweifarben-LIF Messtechnik wurde ein Vergleich der simultanen Erfassung dieser drei Größen mit der sequentiellen Detektion, bei der für die einzelnen Teilmessungen jeweils lediglich ein Tracer zum Einsatz kommt, mit sehr guter Übereinstimmung durchgeführt. Die Methodenentwicklung erfolgte überwiegend an einem optisch zugänglichen Forschungsmotor, der unter anderem unter Zuführung von vorgemischtem Restgas zur Untersuchung unterschiedlicher Restgasraten betrieben wurde. Zur Entwicklung der Zweiwellenlängen-Zweifarben-LIF Messtechnik und deren Einsatz zur Untersuchung unterschiedlicher interner Restgasstrategien kam ein optisch zugänglicher Prototyp mit ein- und auslassseitiger Nockenwellenverstellung zum Einsatz. Die Ergebnisse dieser Arbeit zeigen eine deutlich schnellere Gemischhomogenisierung für den Fall einer drallüberlagerten Tumbleströmung im Vergleich zu einer reinen Tumblestruktur. Zudem hat die zusätzliche Drallstruktur eine schneller ablaufende Verbrennung zur Folge. Da sich diese Auswirkungen auch für Betriebspunkte mit hohen Restgaskonzentrationen aufzeigen lassen, stellt die Überlagerung einer zusätzlichen Drallkomponente ein probates Mittel dar, die Restgasverträglichkeit zu steigern, was wiederum zusätzliche Freiheitsgrade in der Motorabstimmung mit sich bringt. Das Potenzial der simultanen Messtechnik wird an einem Vergleich von Einlasskanalrückführung und Restgasrückhaltung demonstriert. Die Visualisierung der Verteilung des heißen Restgases im Brennraum veranschaulicht dabei dessen Auswirkung auf die Verdampfung des direkteingespritzten Kraftstoffs.<br
Keywords: Ottomotor; Ladungsbewegung; Gemischbildung; Restgaskonzentration; laserinduzierte Fluoreszenz; optische Messtechnik; LIF

Untersuchung der Wechselwirkung von Ladungsbewegung und Restgaskonzentration am DI-Ottomotor mit optischen Messtechniken - Mederer, Thomas; Möller, A.; Wensing, Michael; Leipertz, Alfred (Ladungswechsel im Verbrennungsmotor, 2012)